2011
DOI: 10.1111/j.1740-8709.2011.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

‘It should be the most natural thing in the world’: exploring first‐time mothers' breastfeeding difficulties in the UK using audio‐diaries and interviews

Abstract: Breastfeeding is a practice which is promoted and scrutinised in the UK and internationally. In this paper we use interpretative phenomenological analysis to explore the experiences of eight, British, first-time mothers who struggled with breastfeeding in the early postpartum period. Participants kept audio diary accounts of their infant feeding experiences across a seven day period immediately following the birth of their infant and took part in related semistructured interviews a few days after completion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 48 publications
6
114
0
2
Order By: Relevance
“…Dado lo anterior, se trata de un período lleno de desafíos para cualquier madre, los que pueden acentuarse cuando el proceso no se desarrolla de manera fisiológica o cuando ciertas prácticas del equipo de salud interfieren en él 8,14,15 La experiencia materna de amamantar al hijo se constituye en una vivencia cargada de emociones contradictorias, ya que por una parte la madre espera sentirse feliz con su llegada, pero por otro lado comienza a experimentar emociones negativas hacia ella misma, sus cercanos y a veces hacia su propio niño, en situaciones en dónde las cosas no se dan como ella y su entorno esperaban, escenario que se presenta por ejemplo, cuando la madre tiene dificultades con el amamantamiento 9,16 Los sentimientos de angustia, estrés emocional, cansancio físico y psicológico, se develaron en este estudio como protagonistas, al inicio de la vivencia en la dificultad para amamantar al niño, lo que coincide con lo encontrado en otras publicaciones [17][18][19] . Coincidente con esta investigación, estudios seña-lan que la decisión de amamantar y el deseo de hacerlo a pesar de las dificultades, se basa en la convicción de que la LM es lo mejor para el niño.…”
Section: Discussionunclassified
“…Dado lo anterior, se trata de un período lleno de desafíos para cualquier madre, los que pueden acentuarse cuando el proceso no se desarrolla de manera fisiológica o cuando ciertas prácticas del equipo de salud interfieren en él 8,14,15 La experiencia materna de amamantar al hijo se constituye en una vivencia cargada de emociones contradictorias, ya que por una parte la madre espera sentirse feliz con su llegada, pero por otro lado comienza a experimentar emociones negativas hacia ella misma, sus cercanos y a veces hacia su propio niño, en situaciones en dónde las cosas no se dan como ella y su entorno esperaban, escenario que se presenta por ejemplo, cuando la madre tiene dificultades con el amamantamiento 9,16 Los sentimientos de angustia, estrés emocional, cansancio físico y psicológico, se develaron en este estudio como protagonistas, al inicio de la vivencia en la dificultad para amamantar al niño, lo que coincide con lo encontrado en otras publicaciones [17][18][19] . Coincidente con esta investigación, estudios seña-lan que la decisión de amamantar y el deseo de hacerlo a pesar de las dificultades, se basa en la convicción de que la LM es lo mejor para el niño.…”
Section: Discussionunclassified
“…Researchers often focus on the role of emotions in deterring beneficial health behaviors. Indeed, research has found that women may be unlikely to breastfeed if they fear that the infant may not receive adequate nutrition (Brown, Raynor, & Lee, 2011;Williamson, Leeming, Lyttle, & Johnson, 2012) or that breastfeeding may damage their physical appearance (Hannon, Willis, Bishop-Townsend, Martinez, & Scrimshaw, 2000;Nabulsi, 2011). However, research has suggested that some, more complex, emotions (e.g., pride, regret, guilt, and shame) may serve a self-regulatory role and thus promote beneficial behaviors (Giner-Sorolla, 2001; Van der Schalk, Bruder, & Manstead, 2012).…”
Section: Social Cognitive and Emotional Factorsmentioning
confidence: 99%
“…Meeting participants to explain how the app works would give the most thorough introduction to the technology, and allow questions to be asked and tasks practiced. This has been employed by researchers undertaking audio-visual methods, to ensure participants are sufficiently briefed and familiar with the devices (Bolger, Davis and Rafaeli, 2003;Duke, 2012;Williamson et al, 2011). However one of the benefits of using smartphones is being able to easily access and include a geographically diverse sample (MacKerron and Mourato, 2013;Patel et al, 2013); if researchers are required to meet with participants, this would be negated, or at least it would make it costly.…”
Section: Adequately Preparing Participantsmentioning
confidence: 99%
“…For example, researchers can now send questions to, and receive responses from, participants in real time'. Diary-based methods have not generally followed advances in technology, with empirical studies still overwhelmingly providing participants with audio or video equipment (see for example Cherrington and Watson, 2010;Tamminen and Holt, 2010;Williamson et al, 2011) or maintaining the written format (see for example Day and Thatcher, 2009;Duke, 2012). One example where advances in technology have been utilised in audiovisual methods is Plowman and Stevenson's (2012) study that collected qualitative data by asking parents to use their mobile phone to take and send images for a family time use study.…”
Section: Introduction: Mobile Phones Smartphones and Applications Inmentioning
confidence: 99%